2016
DOI: 10.1002/pon.4257
|View full text |Cite
|
Sign up to set email alerts
|

Truth telling in Taiwanese cancer care: patients' and families' preferences and their experiences of doctors' practices

Abstract: Taiwanese medical educational policies need to be revised to better equip doctors to practice truth telling in accordance with the preferences of cancer patients and families. Communication skills training should be prioritized for doctors who refrain from truth telling in actual practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Similar results have been presented in other studies . Moreover, Gan's quantitative study found that physicians were less positive toward cancer diagnosis disclosure (CDD) than patients and family members, consistent with Tang's study results …”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results have been presented in other studies . Moreover, Gan's quantitative study found that physicians were less positive toward cancer diagnosis disclosure (CDD) than patients and family members, consistent with Tang's study results …”
Section: Introductionsupporting
confidence: 89%
“…Nurses should actively participate in cancer diagnosis delivery, and more collaboration between nurses and physicians must occur.found that physicians were less positive toward cancer diagnosis disclosure (CDD) than patients and family members, consistent with Tang's study results. 17,18 Although physicians hold the responsibility and authority for CDD, nurses are active participants in the diagnosis process and prognosisrelated communication. 19 The exact roles and responsibilities of nurses during CDD are not well delineated.…”
mentioning
confidence: 99%
“…An early survey of international oncologists indicated a clear trend toward more open cancer disclosure in all cultures; however, the percentage of patients who are informed about their illness and participate in decision-making is highest in Western countries, and Asian cultures continue to lag behind in this trend. 13 For example, Jenkins et al 14 documented that almost all patients in the United Kingdom wanted to know whether their illness was cancer and if it was terminal; however, the surveys of other cultural groups indicate that the disclosure of cancer and prognostic information is undesirable. Compared with Western family caregivers, the caregivers in Asian countries are more likely to withhold unfavorable information from patients at the patients’ request and to give treatments with unproven effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Item responses are rated on a 5‐point scale from 1 (extremely unimportant) to 5 (extremely important) 9 25 Higher score indicates that the healthcare providers' truth‐telling perception better met the truth‐telling preferences of patients and their caregivers 5 26 We used the TTQ to measure APNs' perception of cancer truth‐telling; the Cronbach's α of the overall scale measured at different time points was 0.93–0.94, and the four subscales was 0.62–0.93.…”
Section: Methodsmentioning
confidence: 99%